New rice thresher - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
In Mali, 450 new Vortex Ricefan threshing machines have replaced old tractor-drawn equipment. The Vortex threshers are diesel-powered and weigh only 120-150 kg, and thus are easily handled by the village associations which manage them from the...